Complexos de rutênio (II) contendo 2-mercaptoimidazol e derivados: síntese, caracterização e avaliação da atividade biológica - Garbin Sobrinho, Larissa Lorenn (2015)
This work describes the synthesis, characterization and leishmanicidal activity of four new complexes of ruthenium(II) of the type cis-[Ru(N-S)(dppm)2], where dppm = 1,1- bis(diphenylphosphine)methane and N-S corresponds to the ligands 2-mercaptoimidazole, 2- mercapto-1-methylimidazole, 2-mercaptobenzimidazole and 2-mercapto-4-phenylimidazole. The obtained compounds were characterized by elemental analysis (CHNS), infrared spectroscopy (ATR-FTIR), ultraviolet-visible spectroscopy (UV-Vis), phosphorus and proton nuclear magnetic resonance (NMR), mass spectrometry, cyclic voltammetry and the complex containing the ligand 2-mercapto-1-methylimidazole was also characterized by X-ray diffraction crystallography which confirmed the proposed structures. All the complexes and the precursor cis-[RuCl2(dppm)2] were assayed against species of Leishmania (L.) amazonensis, (V.) braziliensis and (L.) infantum and cytotoxicity assays on murine peritoneal macrophages. The results showed that all compounds exhibit leishmanicidal activity and that for the species L. (L.) amazonensis all derivatives were more active than the precursor complex, with IC50 values in the range of 1,19 to 6,32 mmol L-1, depending of the compound. The complex containing 2-mercaptoimidazole was shown as the most active against the three species of Leishmania and showed the best selectivity index compared to murine macrophages.